1991
DOI: 10.1136/jech.45.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Acute closed angle glaucoma and sunshine.

Abstract: Study objective-The aim was to examine a possible association of amount of sunshine and risk for acute closed angle glaucoma.Design-This was a retrospective analysis of hospital discharge registry data, linked to meteorological data for the same period.Setting-The study was a national survey using hospital discharge data for the whole of Finland over a 10 year period.Participants-All subjects with the acute closed angle glaucoma diagnosis from the hospital discharge registry were collected for the years 1972 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(2 reference statements)
0
8
0
1
Order By: Relevance
“…119 Conversely, a Finnish study assessing the association between sun exposure and risk for acute ACG suggested that the number of hours without sunshine is positively associated with the incidence of acute closed angle glaucoma, when other meteorological variables are controlled for. 120 Acute attacks were also reported to occur more frequently in the same population group in winter and autumn than summer or spring. 120 A common factor among all these studies and environmental effects is thought to be that during adverse weather conditions people tend to stay indoors.…”
Section: Nebmentioning
confidence: 99%
See 1 more Smart Citation
“…119 Conversely, a Finnish study assessing the association between sun exposure and risk for acute ACG suggested that the number of hours without sunshine is positively associated with the incidence of acute closed angle glaucoma, when other meteorological variables are controlled for. 120 Acute attacks were also reported to occur more frequently in the same population group in winter and autumn than summer or spring. 120 A common factor among all these studies and environmental effects is thought to be that during adverse weather conditions people tend to stay indoors.…”
Section: Nebmentioning
confidence: 99%
“…120 Acute attacks were also reported to occur more frequently in the same population group in winter and autumn than summer or spring. 120 A common factor among all these studies and environmental effects is thought to be that during adverse weather conditions people tend to stay indoors. This may increase the likelihood of a mydriaticinduced acute ACG attack due to pupillary dilation and a subsequent spike in IOP.…”
Section: Nebmentioning
confidence: 99%
“…8 AAC most commonly occurs during the early evening hours and its incidence is also correlated with the number of hours without sunshine. 9,10 While it is tempting to hypothesize that diurnal variation of static parameters plays a role in the pathogenesis of angle closure disease, such variation has never been clearly demonstrated in healthy or diseased eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Teikari et al . reported that the incidence of acute attack of PACG was higher in winter and autumn compared with spring and summer 21 . However, in Taiwan, hospital admission rates of PACG were significantly higher in March and with increased relative humidity 5 .…”
Section: Discussionmentioning
confidence: 93%
“…Meteorological conditions have previously been reported to be associated with the attack of PACG, and early significant results were only considered to be associated with shortened duration of sunshine. In Finland, an increase in the incidence of acute angle closure glaucoma was noted whenever the number of hours without sunshine increased 21 . Teikari et al .…”
Section: Discussionmentioning
confidence: 99%